TAFSIR AYAT TENTANG PRODUKSI DALAM EKONOMI SYARIAH - Sya’idun Sya’idun (Investama : Jurnal Ekonomi dan Bisnis, 2022)
Production is a process that has existed on Earth since humans first inhabited it. the word production in Arabic with the word "al-Intaj", which is literally interpreted as ajadu sil'atin (creating or making something) or (clear services by demanding assistance in combining production elements within a limited time frame). Production activities are a link in the chain of consumption and distribution, they produce goods and services that are then consumed by consumers. Without production, economic activity will stop, and vice versa. To produce goods and services, production activities involve many factors of production. In the form of a fundamental implementation of production and economic activities as a whole, among other things, all production activities must be related to Islamic moral and technical order, and production activities must pay attention to social aspects, economic problems will arise not only due to scarcity but more complex factors